(untitled) (Revista Rupturas, 2021)
This article shows the main findings obtained from the experience of observing an unprecedented process in the Costa Rican electoral political history, through which the citizens of Río Cuarto had the possibility of choosing the political and administrative center of their canton. The team of Centro Agenda Joven (UNED) participated as an exceptional witness. Using a mixed methods approach, it was possible to determine that the majority of young voters perceive politics with commitment, enthusiasm and even passion, relegating indifference and disgust towards electoral activities. This population sector uses its political rights, both in logistical aspects, as well as in coordination and supervision. Likewise, the investigation registered various manifestations about the responsibility that young people should assume in a historical moment like this, in which they began the path towards the construction of a cantonal identity, which they found in the electronic media and social networks, tools of great value to assume responsibility and leadership in the process.